Highly Active Antiretroviral Therapy (HAART) - “Sulfonyl”, and anal cancer outcomes from patients living with HIV: a retrospective cohort - Raelson Rodrigues Miranda; Erika Andrade Rocha; Amanda Acioli de Almeida Robatto; Denis Artico Galhera; Carolina Ribeiro Victor; Karim Yaqub Imbrahim; Camila Motta Venchiarutti Moniz (Infectious Agents and Cancer)
Abstract Background Although anal cancer is a rare malignancy, its incidence is up to 30 times higher among individuals living with HIV. Recent evidence suggests that Highly Active Antiretroviral Therapy (HAART) regimens containing sulfonyl groups may exhibit antitumor properties. Based on these findings, we hypothesize that HAART regimens incorporating sulfonyl-containing compounds could influence oncologic outcomes in HIV-positive patients undergoing definitive chemoradiotherapy (CRT) for anal cancer. Methods From a cohort of 537 patients with stage I–III invasive anal cancer treated between August 2010 and April 2022, 56 HIV-positive patients who underwent definitive chemoradiotherapy were included in the analysis. . Results Most patients were male. The mean age was 52 years in the non-sulfonyl-HAART group and 53 years in the sulfonyl-HAART group. The mean CD4 count was significantly higher in the non-sulfonyl group compared to the sulfonyl group (523 vs. 287 cells/mm³, p = 0.02). Grade 3–4 toxicities occurred in 60% and 38% of patients, respectively (p = 0.18). Chemotherapy dose reductions were required in 10% of the non-sulfonyl group and 8% of the sulfonyl group (p = 1.0). Treatment discontinuation during chemoradiotherapy occurred in 17% vs. 23% of patients, respectively (p = 0.7). The overall response rate at 6 months post-treatment was significantly higher in the sulfonyl-HAART group (100%) compared to the non-sulfonyl group (20/36; 55.6%), Odds Ratio (OR) 0.00, 95% CI: 0–0.72, p = 0.004). After adjustment, CD4 count was not associated with treatment response (logistic regression OR: 1.00; 95% CI: 0.99– 1.00, p = 0.3). The median progression-free survival (PFS) in the non-sulfonyl-HAART group was 70 months (p = 0.45), and overall survival (OS) was similar between groups (p = 0.6); the median OS was not reached in the sulfonyl-HAART group. In the Cox proportional hazards model, age, clinical stage, and lack of response to CRT at 6 months were independent predictors of worse survival. ( Conclusion HIV-positive patients with anal cancer who received sulfonyl-containing HAART during definitive chemoradiotherapy demonstrated a significantly higher overall response rate at 6 months, independent of baseline CD4 count. However, no significant differences were observed between the sulfonyl and non-sulfonyl groups in terms of treatment-related toxicities, treatment discontinuation, progression-free survival, or overall survival.